2018
DOI: 10.3389/fpsyg.2018.00314
|View full text |Cite
|
Sign up to set email alerts
|

Who Cares for Those Who Take Care? Risks and Resources of Work in Care Homes

Abstract: Over the years – due to the aging population, the process of corporatisation and a demand for a higher quality of services – professionals who work in Care Homes have been exposed to an increasing risk of physical and emotional malaise because of the number of challenges they’ve been asked to manage. Given these factors, there is a growing interest in the study and understanding of professions in geriatric care settings. In the literature there is a prevalence of quantitative studies offering an overview in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…Finally we would like to emphasize that in previous qualitative studies (Gozzoli et al, 2014(Gozzoli et al, , 2018aScaratti et al, 2014Scaratti et al, , 2017Frascaroli et al, 2016;Gorli et al, 2016;Marta et al, 2016;Saita et al, 2016;Tamanza et al, 2016) we found that the living and working together style that characterizes an organization determines the organizational generative possibility in creative and relational terms. Having found that only a non-destructive living and working together style can protect this generative dynamic, we believe that it is important to continue our studies to better understand what happens in destructive living and working together styles.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Finally we would like to emphasize that in previous qualitative studies (Gozzoli et al, 2014(Gozzoli et al, , 2018aScaratti et al, 2014Scaratti et al, , 2017Frascaroli et al, 2016;Gorli et al, 2016;Marta et al, 2016;Saita et al, 2016;Tamanza et al, 2016) we found that the living and working together style that characterizes an organization determines the organizational generative possibility in creative and relational terms. Having found that only a non-destructive living and working together style can protect this generative dynamic, we believe that it is important to continue our studies to better understand what happens in destructive living and working together styles.…”
Section: Resultsmentioning
confidence: 77%
“…In this sense, Gozzoli's (2016a,b) perspective on "Living and working together in organizations" (from now on LWTO) could be significant to enrich the scientific dialogue on organizational creativity. This perspective, as emerges from various empirical qualitative studies (Gozzoli and Frascaroli, 2012;Gozzoli et al, 2014Gozzoli et al, , 2018aScaratti et al, 2014Scaratti et al, , 2017Frascaroli et al, 2016;Gorli et al, 2016;Marta et al, 2016;Saita et al, 2016;Tamanza et al, 2016;D' Angelo et al, 2018), aims to consider variables of interaction and relationship involved in the definition of the living and working together style to better understand their influence on creativity and innovative processes. In fact, a generative living and working together environment, where professionals are allowed to deal with the Otherness with an open dialogue, is itself directly linked to creativity and innovation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, besides mapping the more "conventional" forms of welfare, one of the first useful guidelines that emerged from this study is that it is important to allow these more implicit dimensions to emerge and have an awareness of them. It is also worth specifying that this does not just imply mapping and highlighting actions, but also understanding the representations related to welfare and the connection with the organisational life in which these actions collocate themselves [2,[33][34][35][36][37]. The challenge that arises-especially for SMEs-is to preserve what is known, "familiar" and that gives security, which maintains a stable identity, and acknowledge the urge to change and evolve to respond to new internal and external demands.…”
Section: Discussionmentioning
confidence: 99%
“…To be sustainable, in this sense, every organizational/managerial process and practice should be underpinned by specific "pillars" [19,20], such as participation, equity and justice [21], co-creation of value [22], individual and collective capital promotion and regeneration [23,24]. Rather than aiming at avoiding exploitation, depletion and irreparable alteration, from this perspective sustainability focuses on the promotion of individual and collective well-being [25][26][27], and is concerned with stakeholder engagement and value generation on multiple fronts [28]. Further, sustainability requires the construction of "authentic meanings for individuals and communities, underlining the importance of connections, meaning and purpose" [25] (p. 2).…”
Section: Theoretical Frameworkmentioning
confidence: 99%